THE ANALYSIS OF THE RISK FACTORS OF UNSAFE BEHAVIOR AMONG CONSTRUCTION WORKERS IN TANGERANG - Andrea, Dio Rafly; Handayani, Rini; Situngkir, Decy; Millah, Izzatu (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: The Minister of Manpower stated that the construction sector contributed to the highest number of work accidents. The cause of construction-sector work-accidents as much as 40% came from unsafe behavior from workers. Unsafe behavior is described as the possibility of individuals not following safety standards, procedures, instructions, and criteria specific to the work that the organization applies to. According to a preliminary study, 6 out of 10 workers (60%) have unsafe behavior while working. Purpose: To find out the risk factors of unsafe behavior in construction workers at the Cartenz apartment construction project in Tower D, PT. Nusa Raya Cipta, Tangerang in 2021. Method: A cross-sectional design was used in this present study. The population and sample included 42 workers that were used as total sampling technique. The primary data were collected by questionnaire, whereas the analysis was done with the Chi-square test in bivariate analysis. Result: The analysis showed that 40.5% workers had unsafe behavior, 45.2% had poor knowledge, 31% showed bad attitudes, 52.4% had new work period, and 42.9% had poor supervision. Bivariate analysis indicated that knowledge (p-value 0.016), attitude (p-value 0.028), work period (p-value 0.004), and supervision (p-value 0.041) are associated with unsafe behavior. Conclusion: The risk factors of unsafe behavior in construction workers in Tangerang include knowledge, work period, attitudes, and supervision.